Governmental microcredit and poverty reduction - PHAM, Thi Tuyet Trinh (KDI School, 2016)
The thesis aims to assess the poverty targeting of the preferential credit programme for the poor from Vietnam Bank for Social Policies and its impacts on household welfare, in terms of income from profits per capita, consumption expenditure per capita, and food consumption expenditure per capita, in rural areas of Vietnam. Using data from Vietnam Household Living Standards Surveys from 2004 to 2012, the study finds that the programme has not sufficiently targeted the poor, with low coverage rate and high leakage rate. Likewise, the programme seems not so pro-poor, that is, it fails to target the poorer strata of the rural households. To examine the impacts of the programme, the study employs household and commune fixed-effects to control for unobserved and time-invariant attributes that may both affect the outcome variable and the participation status of the households. The study also uses an instrumental variable which is access to credit to control for other endogeneity problems. With three different data panels constructed: 2004-2006, 2006-2008, and 2010-2012, estimation results suggest that the microfinance programme has statistically significant positive impact on household income from profits for the first period. The impacts, however, turned out to be insignificant in the latter two periods 2006-2008, and 2010-2012, even though the coefficients still suggest a positive effect. The study also finds no evidence on the impacts of participating in this programme on other household welfare proxies, including consumption expenditure, and food consumption expenditure.
Thesis(Master) --KDI School:Master of Public Policy,2016